Progress in research and applications of Polyphenylene Sulfide blends and composites with carbons. (15th March 2021) - Chen, Guowei; Mohanty, Amar K.; Misra, Manjusri
Abstract: Polyphenylene sulfide (PPS) is a type of thermoplastic polymer with high thermal and mechanical performance that has wide applications in various industries, such as precise electronics, electrical devices, chemical containers, automobile and aerospace components, etc. By adding carbon in different forms (including carbon fibers, carbon nanotubes, graphite, graphene and carbon black) into the PPS matrix, one is able to form composites that have better mechanical properties and multiple functionalities. The addition of carbons can greatly improve the mechanical properties, tribological properties, post-fire structural integrity and electrical/thermal conductivity of the PPS blends and composites. Due to the above reasons, the PPS/carbon blends and composites have the potential to serve as structural components, bipolar plates and separators, etc. However, the current industrialized petroleum-based carbons are somewhat harmful to the environment and would also increase the manufacturing cost of composite materials. This paper provides an overview of the PPS/carbon blends and composites from recent peer-reviewed research and their applied and potential applications. The possibility is discussed that bio-carbon can be developed as an alternative for petroleum-based carbon fillers used in PPS composites. Graphical abstract: Image 1 Highlights: The progress on PPS/carbon composites from recent peer-reviewed researches are reviewed. The applied uses of PPS/carbon composites as structural materials of aircrafts and household appliances are overviewed. The potential applications of PPS/carbon composites as bipolar plates and separation membrane are discussed. The major challenges on the innovation of PPS/carbon composites are discussed and critically analyzed. Biocarbon as a sustainable alternative for petroleum-based carbons can be used in developing new PPS/carbon composites.